Efektivitas Edukasi Sebaya Berbasis Sekolah terhadap Pengetahuan, Sikap dan Perilaku Pencegahan Diabetes Melitus pada Remaja - Nursyamsiyah, Nursyamsiyah; Cahyaningsih, Henny; Ariyanti, Metia; Mulyanti, Sri; Tarnoto, Koko Wahyu (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: Diabetes Mellitus (DM) has become a global health concern with a rapidly increasing prevalence, including among adolescents. Early prevention efforts are essential and can be implemented through school-based peer education approaches. Objective: To determine the effectiveness of school-based peer education on knowledge, attitudes, and behaviors related to diabetes mellitus prevention among adolescents. Methods: A quasi-experimental design with a pretest and posttest control group was employed. The sample consisted of 90 adolescents, divided equally into the intervention and control groups (45 participants each). The intervention group received peer education through four weekly sessions, each lasting 60 minutes, while the control group did not receive any intervention. Data were collected using validated and reliable questionnaires assessing knowledge, attitudes, and behaviors related to diabetes mellitus prevention. The analysis employed the Mann-Whitney U test, the Wilcoxon signed-rank test, the independent t-test, and the paired t-test. Results: The intervention group exhibited a considerably greater increase in knowledge scores compared to the control group (p=0.001). Attitude scores improved in the intervention group but declined in the control group, with a statistically significant difference (p = 0.005). Despite a marginally bigger improvement in behavior scores within the intervention group, the difference lacked statistical significance (p=0.802). Conclusion: School-based peer education improved adolescents’ knowledge and attitudes toward diabetes mellitus prevention but did not significantly influence preventive behaviors. Therefore, sustainable educational interventions that are integrated into school programs and support from various stakeholders